Kamus Kawi - Jawa menurut Kawi - Javaansch Woordenboek C.F. Winter Sr dan R. Ng. Ranggawarsito ; alih aksara oleh Asia Padmopuspito, A. Sarman Am - WINTER SR, C.F; RANGGAWARSITO, R. Ng; PADMOPUSPITO, Asia; SARMAN Am, A (1990)
xii, 311 hlm 23 cm